Juniper Berry - Kozlowsky, M. P.; Madrid, Erwin (New York : Walden Pond Press, 2011)
When eleven-year-old Juniper begins to suspect something is wrong with her mother and father, she and her friend Giles discover they have been selling their souls, pieces at a time, to a silver-tongued creature in a terrifying fairy-tale underworld.
Wilson's Children, September 2011
Wilson's Junior High School, September 2011
Booklist, March 2011
Horn Book, October 2011
Bulletin (Center for Children's books), May 2011
5.2.
Keywords: Families -- Juvenile fiction; Soul -- Juvenile fiction; Ghouls and ogres -- Juvenile fiction; Supernatural -- Juvenile fiction; Family life -- Fiction; Soul -- Fiction; Ghouls and ogres -- Fiction; Supernatural -- Fiction